2018
DOI: 10.2196/mhealth.8849
|View full text |Cite
|
Sign up to set email alerts
|

Patient and Family Engagement in the Design of a Mobile Health Solution for Pediatric Asthma: Development and Feasibility Study

Abstract: BackgroundAsthma is a highly prevalent, chronic disease with significant morbidity, cost, and disparities in health outcomes. While adherence to asthma treatment guidelines can improve symptoms and decrease exacerbations, most patients receive care that is not guideline-based. New approaches that incorporate shared decision-making (SDM) and health information technology (IT) are needed to positively impact asthma management. Despite the promise of health IT to improve efficiency and outcomes in health care, ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 15 publications
0
31
0
2
Order By: Relevance
“…There were no definitions or conceptualisation of public involvement in almost half of articles ( n = 43, 46.2%) [ 40 – 82 ]. Where reported, public participant numbers ranged from 4 [ 83 ], to an estimated 1200 [ 84 ], though no numbers were given in 13 articles (14.0%) [ 45 , 47 , 49 , 58 , 69 , 72 74 , 77 , 85 88 ], and incomplete or estimated numbers were provided in a further 25 (26.9%) [ 40 , 43 , 44 , 50 , 51 , 56 , 57 , 61 – 63 , 66 , 76 , 82 , 84 , 89 99 ]. Some authors provided demographic data of public participants, such as age, gender, medical condition and/or race, however, there was no detail provided in more than half of articles ( n = 52, 55.9%) [ 37 , 38 , 40 , 41 , 43 – 51 , 55 , 58 , 59 , 61 , 63 , 66 , 68 , 69 , 71 74 , 77 , 79 , 81 – 88 , 93 , 95 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were no definitions or conceptualisation of public involvement in almost half of articles ( n = 43, 46.2%) [ 40 – 82 ]. Where reported, public participant numbers ranged from 4 [ 83 ], to an estimated 1200 [ 84 ], though no numbers were given in 13 articles (14.0%) [ 45 , 47 , 49 , 58 , 69 , 72 74 , 77 , 85 88 ], and incomplete or estimated numbers were provided in a further 25 (26.9%) [ 40 , 43 , 44 , 50 , 51 , 56 , 57 , 61 – 63 , 66 , 76 , 82 , 84 , 89 99 ]. Some authors provided demographic data of public participants, such as age, gender, medical condition and/or race, however, there was no detail provided in more than half of articles ( n = 52, 55.9%) [ 37 , 38 , 40 , 41 , 43 – 51 , 55 , 58 , 59 , 61 , 63 , 66 , 68 , 69 , 71 74 , 77 , 79 , 81 – 88 , 93 , 95 110 ].…”
Section: Resultsmentioning
confidence: 99%
“…An interactive digital solution study showed the feasibility and benefits of deploying user-centric design methods that engage real patients and caregivers throughout the health technology design process [ 29 ]. Another study proposed a paradigm shift—from providing features that are easy to implement technologically to using an approach in which apps are designed to deliver theoretically grounded preferred components [ 30 ]. This app was developed and modified based on theoretically grounded preferred components of our previous studies [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globalement, ces démarches s'inscrivent dans les techniques de développement agile et de design centré sur les besoins des utilisateurs, permettant d'aboutir rapidement à un résultat conforme aux attentes. 10 Enjeux liés à la réutilisation de l'information des SIH Les aspects techniques relatifs aux fonctions d'arrière-plan de l'application (back-end, notamment la logique de communication avec le SIH) ne seront pas abordés en détail ici. Toutefois, il est important de souligner que les enjeux majeurs ont concerné l'interopérabilité (développer Concerto pour le rendre compatible avec d'autres SIH dans le futur), la sécurité (connecter une tablette au SIH) mais surtout la transformation des données présentes dans le SIH en information faisant sens pour les patients.…”
Section: Du Hackathon Au Financementunclassified